Development of a Diagnostic Oligonucleotide DNA Probe for the Rapid Detection of Vibrio Cholerae O139 - Khaw, Aik Kia (2001)
Vibrio cholerae O139 Bengal emerged as the second etiologic agent of cholera in the Indian subcontinent in late 1992, it then spread to several neighboring countries and also some developed countries. V. cholerae O139 Bengal is closely related to V. cholerae O1 E1 Tor strains associated with the seventh pandemic, and it causes a disease which is virtually indistinguishable from cholera caused by V. cholerae O1. V. cholerae O139 Bengal and V. cholerae O1 E1 Tor share several phenotypic and genotypic properties. However, all the genes of the rfb complex which encode the O antigen in V. cholerae 01 El Tor have been found deleted in V. cholerae O139. In their place, there is a new chromosomal region detected. Based on a published sequence, six set of V. cholerae O139 primers have been designed. Primer combination Sl -AS2 (5'-AGATGCCGAAGACTATAA-3' and 5'-GAGGAATAACAACTGAGA-3') was found to be specific for detection of V. cholerae O139 in a polymerase chain reaction (peR) assay, as they produced an amplicon of 520 bp from all tested pure cultures of V. cholerae O139 strains but not from 39 pure cultures of other bacteria. The newly designed primer combination has been used to develop a, diagnotic kit for the identification of V. cholerae O139 in our laboratory.